A true silent compartment syndrome in a competent sensate patient: Case report. (August 2017) - Hitz, Myrielle; Donner, Georg; Decking, Jens
Abstract : A 21-year-old competent sensate man developed a compartment syndrome without significant pain after intramedullary nailing of an open short oblique fracture of the distal tibial shaft (AO 42-A2). A droping foot and reduced sensation in the first web space was noticed 5 days after the operation. Until then, the patient was comfortable with Paracetamol and Novaminsulfon, but the compartment pressure measurement of the anterior compartment revealed a pressure of 80mmHg. At emergency fasciotomy of all four compartments of the lower leg, the muscles of the anterior compartment were dusky, sparely bleeding and not contracting on stimulation. After 3 weeks of regular debridement of grey muscle parts and continuous vacuum pressure dressing the tibialis anterior muscle was still necrotic and the extensor digitorum and hallucis longus muscle partially necrotic. The patient underwent complete myectomie of the tibialis anterior muscle and the distal parts of the extensor digitorum and extensor hallucis muscles. The compartment was covered with a functional gracilis free flap and a thiersch graft from the anterolateral thigh. The development of pain, that is not controllable with analgetics and out of proportion to the injury sustained is said to be the first and most reliable symptom for the increase of compartment pressure. Our patient never reported pain of an intensity of more than 2/10 on routine pain scale monitoring. In the literature we found little cases of competent sensate adult patients. We think it is important to know, that the absence of significant pain does not exclude a compartment syndrome. We want to increase the sensitivity for a high index of suspicion after suitable trauma and motivate to messure compartment pressure even in patients with no significant pain. Background: A 21-year-old competent sensate man developed a compartment syndrome without significant pain after intramedullary nailing of an open tibial shaft fracture. Because of complete paresis of the nervus peroneus profundus 5 days postoperatively he underwent myectomy of the anterior compartment covered with a functional gracilis free flap. The development of pain out of proportion to the injury sustained is said to be the first and most reliable symptome for the increase of compartment pressure. This was not the case in our patient. We think it is important to know that the absence of significant pain does not exclude a compartment syndrome. We want to increase the sensitivity for a high index of suspicion after suitable trauma and motivate to measure compartment pressure even in patients with no significant pain. Case presentation: A 21-year-old man sustained an open isolated short oblique fracture of the distal tibial shaft (AO 42-A2) when he was caught by a slow driving car on a parking lot. The lower leg compartments were soft at initial assessment, there was no neurovascular deficit and the patient was otherwise healthy. Uneventful intramedullary nailing was performed. Postoperatively, the patient was comfortable with Paracetamol and Novaminsulfon and never reported of pain of an intensity of more than 2/10 on routine pain scale monitoring. The compartments of the lower leg were palpated daily by the surgeon. On the 5th postoperative day a droping foot was noticed. Clinical examination revealed a complete paresis of the foot elevator, reduced sensation in the first web space, slightly tense anterior compartment and the compartment pressure measurement of the anterior compartment was 80mmHg. At emergency fasciotomy the muscles of the anterior compartment were dusky, sparely bleeding and not contracting on stimulation. After 3 weeks of regular debridement and continuous vacuum pressure, dressing the tibialis anterior muscle was still necrotic and the extensor digitorum and hallucis longus muscle partially necrotic. The patient underwent myectomie of the necrotic muscles. The compartment was covered with a functional gracilis free flap and a thiersch graft. Outcomes: One year after trauma the tibial fracture was healed. The paresis of the foot elevator persisted. The neurologic examination confirmed complete denervation of the functional gracilis muscle. The force of the extensor hallucis and digitorum longus muscle was tested M3. The patient was ambulating painfree and happy with an orthotic brace and back to his work as a car mechanic. We offered a transfer of the tibialis posterior tendon but he refuses until now. Discussion: In the literature, we found only one case report from Badhe (2008) with 4 competent sensate adult patients with a silent compartment syndrome. A metaanalysis of Todd Ulmer (2002) reports about a sensitivity for the cardinal symptoms of 13-19%. The negative predictive value was 97-98. He stated, an acute compartment syndrome can be ruled out with 98% certainty if no clinical symptoms are present. Al-Dadah (2008) compared the outcome after clinical monitoring versus continuous compartment measurements. Additional invasive pressure measurements did not lead to higher fasciotomy rates. McQueen (2013) showed on 979 monitored patients a sensitivity of intracompartmental pressure monitoring of 94%, a specificity of 98%, a positive predictive value of 93% and a negative predictive value of 99%. A low threshold for compartment measurements even in patients with little clinical symptoms seems appropriate.